A kind of graphene slurry and its preparation method and application
Through the combination of nanosilica-graphene composite and polyamino cationic perylene imide dispersants, the problem of graphene prone to agglomeration in anticorrosion coatings is solved, the dispersion and corrosion resistance are improved, and the corrosion protection time is extended , and maintains stable performance under high temperature storage conditions.
Patent Information
- Application Number
- CN202311124130.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-09-01
AI Technical Summary
Graphene is prone to agglomeration in anticorrosion coatings, resulting in difficulty in dispersion. The increase of conventional dispersants reduces adhesion performance and corrosion protection time.
Nanosilica-graphene composites are combined with polyamino cationic perylene imide dispersants to prevent graphene agglomeration through electrostatic attraction and react with epoxy resin to fix it to enhance anticorrosion performance.
The dispersion and corrosion resistance of graphene slurry are improved, the corrosion resistance time is extended, and there is no significant change in physical and chemical properties under accelerated storage conditions.
Smart Images

Figure BDA0004427627640000011 
Figure BDA0004427627640000021 
Figure BDA0004427627640000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-corrosion coatings and relates to a graphene slurry and a preparation method and application thereof. Background Art
[0002] Due to the high conductivity of graphene and its high electron mobility, graphene is widely used as an additive in anti-corrosion coatings to provide better cathodic protection and improve the corrosion resistance of the coating. However, the application of graphene in anti-corrosion coatings still faces the technical problem of easy agglomeration of graphene.
[0003] Due to the high specific surface area of graphene, graphene will undergo irreversible agglomeration and even rearrange back into a graphite structure, making it very difficult to prepare a stable dispersion of graphene. The main conventional method to solve the dispersion of graphene is to add a large amount of dispersant to the graphene slurry. The addition of a large amount of dispersant reduces the adhesion performance of the graphene slurry and shortens the corrosion protection time of the graphene slurry. Therefore, inventing a graphene slurry with good dispersibility and better corrosion protection performance is a technical problem that needs to be solved urgently. Summary of the invention
[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a graphene slurry and a preparation method and application thereof.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a graphene slurry, wherein the raw materials for preparing the graphene slurry include the following components in parts by weight:
[0007]
[0008]
[0009] The dispersant includes a polyamino cationic perylene imide dispersant.
[0010] In the present invention, the nano silicon dioxide and graphene in the nano silicon dioxide-graphene composite are combined more closely, and the graphene agglomeration can be effectively blocked, and when the graphene slurry is used for anticorrosive coating, silicon dioxide can fill the gap defect in the coating, hinder the penetration of corrosion factors, and can cooperate with graphene to improve the anticorrosion performance of the coating. The cation in the polyamino cationic perylene imide dispersant is combined with the anion in the nano silicon dioxide-graphene composite by electrostatic attraction, thereby the interlayer spacing of graphene can be expanded, the graphene agglomeration is prevented, the combination between the graphene sheets is hindered, and the dispersibility is improved. In addition, the dispersant can react with epoxy resin on the one hand, play the curing agent effect, and the nano silicon dioxide-graphene composite can be fixed to the epoxy resin surface on the other hand, not only play the effect of preventing the graphene agglomeration, but also further enhance the overall anticorrosion performance of the coating.
[0011] In the present invention, the raw materials for preparing the graphene slurry are measured in parts by weight, and the amount of epoxy resin used can be 30 parts, 33 parts, 35 parts, 38 parts, 40 parts, 43 parts, 45 parts, 48 parts, 50 parts, 53 parts, 55 parts, 58 parts, 60 parts, etc., but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0012] In the present invention, the raw materials for preparing the graphene slurry are measured in parts by weight, and the amount of solvent used can be 20 parts, 23 parts, 25 parts, 28 parts, 30 parts, 33 parts, 35 parts, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0013] In the present invention, the raw materials for preparing the graphene slurry are measured in parts by weight, and the amount of graphene used can be 3 parts, 3.3 parts, 3.5 parts, 3.8 parts, 4 parts, 4.3 parts, 4.5 parts, 4.8 parts, 5 parts, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] In the present invention, the raw materials for preparing the graphene slurry are measured in parts by weight, and the amount of the nano-silicon dioxide-graphene composite can be 4 parts, 4.3 parts, 4.5 parts, 4.8 parts, 5 parts, 5.3 parts, 5.5 parts, 5.8 parts, 6 parts, 6.3 parts, 6.5 parts, 6.8 parts, 7 parts, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] In the present invention, the raw materials for preparing the graphene slurry are measured in parts by weight, and the amount of the dispersant used can be 3 parts, 3.3 parts, 3.5 parts, 3.8 parts, 4 parts, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] In the present invention, the raw materials for preparing the graphene slurry are measured in parts by weight, and the amount of the wetting agent used can be 1 part, 1.3 parts, 1.5 parts, 1.8 parts, 2 parts, 2.3 parts, 2.5 parts, 2.8 parts, 3 parts, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] In the present invention, the raw materials for preparing the graphene slurry are measured in parts by weight, and the amount of the additive used can be 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Preferably, the polyamino cationic perylene imide dispersant is prepared by the following method:
[0019] Perylenetetracarboxylic dianhydride (PTCDA) and polyethylene polyamine are subjected to reflux reaction in toluene, followed by acidification treatment to obtain the polyamino cationic perylene imide dispersant.
[0020] Preferably, the molar ratio of perylenetetracarboxylic dianhydride to polyethylene polyamine is 1:(0.8-1.2), 0.8-1.2 can be, for example, 0.8, 0.9, 1, 1.1, 1.2, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, the polyethylene polyamine includes triethylenetetramine, which has amino groups at both ends to participate in the curing reaction.
[0022] Preferably, the reflux reaction time is 5 to 8 hours, for example, 5 hours, 6 hours, 7 hours, 8 hours, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] Preferably, the acid used in the acidification treatment comprises formic acid.
[0024] Preferably, the wetting agent includes β-hydroxyalkylamide. β-hydroxyalkylamide can also be used as a curing agent. On the one hand, it can react with the epoxy resin to play a role of a curing agent. On the other hand, it can fix the nano-silicon dioxide-graphene composite to the surface of the epoxy resin, which not only prevents the graphene from agglomerating, but also further enhances the overall anti-corrosion performance of the coating.
[0025] Preferably, the wetting agent further comprises n-octanol and / or n-butanol.
[0026] In the present invention, the wetting agent and the dispersant cooperate with each other to achieve a better dispersion effect on the dispersion of the graphene slurry, and enable the graphene slurry to be stored for a long time, that is, the graphene slurry has excellent storage stability.
[0027] Preferably, the nano-silicon dioxide-graphene composite is prepared by the following method:
[0028] (1) mixing graphene oxide with distilled water, then adding ethanol, performing a first ultrasonic treatment to obtain a graphene oxide suspension, then adding an alkaline agent to adjust the pH value of the system to 8-9, performing a second ultrasonic treatment, then adding ethyl orthosilicate, and performing a third ultrasonic treatment to obtain a mixture;
[0029] (2) The mixture is stored at room temperature (25° C.), then centrifuged and washed to obtain the nano-silica-graphene composite.
[0030] Preferably, based on 100 mg of graphene oxide, the amount of ethyl orthosilicate is 0.2-0.8 mL, for example, 0.2 mL, 0.3 mL, 0.4 mL, 0.5 mL, 0.6 mL, 0.7 mL, 0.8 mL, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the time of the first ultrasonic treatment in step (1) is 1 to 3 hours, such as 1 hour, 2 hours, 3 hours, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0032] Preferably, the time of the second ultrasonic treatment in step (1) is 0.5 to 1.5 h, such as 0.5 h, 1 h, 1.5 h, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] Preferably, the time of the third ultrasonic treatment in step (1) is 2 to 4 hours, such as 2 hours, 3 hours, 4 hours, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Preferably, the storage time in step (2) is 1 to 3 days, such as 1 day, 2 days, 3 days, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the solvent comprises n-butanol and / or xylene.
[0036] Preferably, the weight proportion of n-butanol is 9 to 16 parts, for example 9, 10, 11, 12, 13, 14, 15, 16, etc., but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable. The weight proportion of xylene is 11 to 19 parts, for example 11, 12, 13, 14, 15, 16, 17, 18, 19, etc., but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0037] Preferably, the auxiliary agent includes a lubricant and / or a binder.
[0038] Preferably, the weight proportion of the lubricant is 2 to 7 parts, for example 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable. The weight proportion of the binder is 2 to 5 parts, for example 2 parts, 3 parts, 4 parts, 5 parts, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] Preferably, the lubricant comprises polyethylene wax.
[0040] Preferably, the binder comprises bentonite.
[0041] In a second aspect, the present invention provides a method for preparing the graphene slurry as described in the first aspect, the preparation method comprising the following steps:
[0042] (1) mixing a dispersant with a portion of a solvent to obtain a dispersant solution;
[0043] (2) mixing the wetting agent with part of the solvent to obtain a wetting agent solution;
[0044] (3) mixing the wetting agent solution with the graphene and the nano-silica-graphene composite, and then adding the dispersant solution to obtain a premix;
[0045] (4) mixing the premix obtained in step (3) with epoxy resin, remaining solvent and auxiliary agent to obtain the graphene slurry.
[0046] Preferably, in the dispersant solution of step (1), the weight percentage of the dispersant is 30% to 40%, for example 30%, 33%, 35%, 38%, 40%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, in the wetting agent solution of step (2), the weight percentage of the wetting agent is 30% to 40%, for example 30%, 33%, 35%, 38%, 40%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] In a third aspect, the present invention provides an application of the graphene slurry as described in the first aspect in an anti-corrosion coating.
[0049] Compared with the prior art, the present invention has at least the following beneficial effects:
[0050] The graphene slurry provided by the present invention comprises a combination of epoxy resin, solvent, graphene, nano-silicon dioxide-graphene composite, dispersant, wetting agent and auxiliary agent, and the graphene slurry has excellent anti-corrosion performance and dispersibility through the screening and coordinated compounding of specific components, especially the introduction of nano-silicon dioxide-graphene composite and dispersant. Through further screening and optimization of components, the anti-corrosion performance and dispersibility of the graphene slurry are further improved, and the physical and chemical properties of the graphene slurry do not show obvious changes after accelerated storage at 70° C. for 30 days or storage at room temperature for one year. DETAILED DESCRIPTION
[0051] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0052] The nano-silicon dioxide-graphene composite used in the examples and comparative examples of the present invention is prepared by the following method:
[0053] (1) first weighing 16 mL of graphene oxide (containing 160 mg of graphene oxide) and pouring it into 40 mL of distilled water, then adding 400 mL of ethanol, and ultrasonically treating for 2 hours to obtain a uniform graphene oxide suspension, then adding 6 mL of ammonia water to the suspension, adjusting the pH value to 9, and continuing ultrasonically treating for 1 hour, then adding 0.7 mL of tetraethyl orthosilicate, and continuing ultrasonically treating for 3 hours to obtain a mixture;
[0054] (2) The mixture was stored at room temperature (25° C.) for 2 days, then the mixture was centrifuged and washed with ethanol 5 times to remove free silica, finally obtaining the nano-silica-graphene composite, which was stored in distilled water for future use.
[0055] Preparation Example 1
[0056] In this preparation example, a polyamino cationic perylene imide dispersant is provided, comprising the following steps:
[0057] Perylenetetracarboxylic dianhydride (PTCDA) and triethylenetetramine in a molar ratio of 1:1 are refluxed in toluene for 6 hours, and then acidified with formic acid to obtain the polyamino cationic perylene imide dispersant.
[0058] Preparation Example 2
[0059] In this preparation example, a polyamino cationic perylene imide dispersant is provided, comprising the following steps:
[0060] Perylenetetracarboxylic dianhydride (PTCDA) and triethylenetetramine in a molar ratio of 1:0.8 are refluxed in toluene for 5 hours, and then acidified with formic acid to obtain the polyamino cationic perylene imide dispersant.
[0061] Preparation Example 3
[0062] In this preparation example, a polyamino cationic perylene imide dispersant is provided, comprising the following steps:
[0063] Perylenetetracarboxylic dianhydride (PTCDA) and triethylenetetramine in a molar ratio of 1:1.2 are refluxed in toluene for 8 hours, and then acidified with formic acid to obtain the polyamino cationic perylene imide dispersant.
[0064] Examples 1-6
[0065] In the present embodiments 1-6, a graphene slurry is provided respectively, and the specific composition and amount of the raw materials for preparing the graphene slurry are shown in Table 1.
[0066] The preparation method comprises the following steps:
[0067] (1) mixing a dispersant with a portion of a solvent to obtain a dispersant solution, wherein the weight percentage of the dispersant is 35%;
[0068] (2) mixing the wetting agent with part of the solvent to obtain a wetting agent solution, wherein the weight percentage of the wetting agent is 35%;
[0069] (3) mixing the wetting agent solution with the graphene and the nano-silica-graphene composite, and then adding the dispersant solution to obtain a premix;
[0070] (4) mixing the premix obtained in step (3) with epoxy resin, remaining solvent, and additives to obtain the graphene slurry;
[0071] Among them, when there is more than one kind of a certain preparation raw material, different types of the preparation raw materials are first mixed, and then mixed with other raw materials. For example, when the solvent includes n-butanol and xylene at the same time, n-butanol and xylene are first mixed, and then mixed with the dispersant.
[0072] Table 1
[0073]
[0074] The blank spaces in Table 1 indicate that no corresponding raw materials were added.
[0075] Comparative Examples 1-4
[0076] In Comparative Examples 1-4, a graphene slurry is provided respectively, and the specific composition and amount of the raw materials for preparing the graphene slurry are shown in Table 2.
[0077] The preparation method refers to the examples.
[0078] Table 2
[0079]
[0080] The blank spaces in Table 2 indicate that no corresponding raw materials were added.
[0081] The performance test of the graphene slurry provided in the embodiment and the comparative example is carried out, and the test method is as follows:
[0082] (1) Anticorrosion performance: The surface of the tinplate sheet was polished and degreased with acetone and cleaned with anhydrous ethanol, and then the graphene slurry was brushed on it, cured at 70°C for 24 hours, and then dried in a 60°C drying oven for 12 hours. The coating was immersed in 4% NaOH solution and 4% HCl solution respectively, and the number of days when rust spots or wrinkles appeared was recorded, and it was checked every 24 hours.
[0083] (2) Storage stability: The graphene slurry was placed at 70°C for 30 days to observe whether there was any precipitation at the bottom; and the graphene slurry after storage at 70°C for 30 days was tested for corrosion resistance according to the method in (1) above.
[0084] The performance test results are shown in Table 3.
[0085] Table 3
[0086]
[0087] It can be seen from Table 3 that the graphene slurry provided by the embodiment of the present invention has excellent anti-corrosion performance, dispersibility and storage stability (no precipitation after standing at 70°C for 30 days), and after accelerated storage at 70°C for 30 days, its anti-corrosion performance did not show obvious changes.
[0088] Compared with Example 1, the anti-corrosion performance and storage stability of the graphene slurries provided in Comparative Examples 1-4 are significantly reduced.
[0089] The applicant declares that the present invention illustrates the graphene slurry and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A graphene slurry, characterized in that: The raw materials for preparing the graphene slurry include the following components in parts by weight: Epoxy resin 30~60 parts; 20-35 parts of solvent; 3~5 parts of graphene; 4-7 parts of nano-silicon dioxide-graphene composite; 3~4 parts of dispersant; Wetting agent 1~3 parts; 4~12 parts of additives; The dispersant includes a polyamino cationic perylene imide dispersant; The wetting agent includes beta-hydroxyalkylamides.
2. The graphene slurry according to claim 1, characterized in that: The polyamino cationic perylene imide dispersant is prepared by the following method: Perylenetetracarboxylic dianhydride and polyethylene polyamine are subjected to reflux reaction in toluene, followed by acidification treatment to obtain the polyamino cationic perylene imide dispersant.
3. The graphene slurry according to claim 1, characterized in that: The nano-silicon dioxide-graphene composite is prepared by the following method: (1) Graphene oxide is mixed with distilled water, and then ethanol is added, and ultrasonic treatment is performed for the first time to obtain a graphene oxide suspension, and then an alkaline agent is added to adjust the pH value of the system to 8-9, and ultrasonic treatment is performed for the second time, and then ethyl orthosilicate is added, and ultrasonic treatment is performed for the third time to obtain a mixture; (2) The mixture is stored at room temperature, and then centrifuged and washed to obtain the nano-silica-graphene composite.
4. The graphene slurry according to claim 3, characterized in that: Based on 100 mg of graphene oxide, the amount of ethyl orthosilicate used is 0.2-0.8 mL.
5. The graphene slurry according to claim 1, characterized in that: The solvent includes n-butanol and / or xylene.
6. The graphene slurry according to claim 1, characterized in that: The auxiliary agent includes a lubricant and / or a binder.
7. A method for preparing a graphene slurry as claimed in any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) mixing the dispersant with part of the solvent to obtain a dispersant solution; (2) mixing the wetting agent with part of the solvent to obtain a wetting agent solution; (3) mixing the wetting agent solution with the graphene and the nano-silica-graphene composite, and then adding the dispersant solution to obtain a premix; (4) The premix obtained in step (3) is mixed with epoxy resin, the remaining solvent and the auxiliary agent to obtain the graphene slurry.
8. The preparation method according to claim 7, characterized in that: In the dispersant solution of step (1), the weight percentage of the dispersant is 30% to 40%.
9. The preparation method according to claim 7, characterized in that: In the wetting agent solution of step (2), the weight percentage of the wetting agent is 30% to 40%.
10. Use of the graphene slurry according to any one of claims 1 to 6 in anti-corrosion coatings.
